Determining Factors Of Fraud In Government Institutions (Empirical Study on OPD in Malaka Regency) - Kristo Josep Manek; Wahidahwati; Bambang Suryono (Neo Journal of economy and social humanities, 2022)
This study aimed to examine and analyze the effect of internal control, organizational culture, leadership style, compensation suitability, and un-ethic behavior on fraud at the Government Institution of Malaka Sub-district. The research population was all civil servants who worked at Malaka Local Government Organization. Furthermore, the data collection technique used a purposive sampling technique. In this study, there were 153 civil servants chosen as the sample. The study used questionnaires as its research instrument and primary data. Moreover, it was quantitative research. Meanwhile, the data analysis technique used multiple linear regression. According to the findings, this study concluded that internal control had a negative and significant effect on fraud. Similarly, leadership style had a significantly negative effect on fraud. However, un-ethic behavior had a positive and significant effect on fraud. On the contrary, both organizational culture and compensation suitability did not have a significant effect on fraud at the Government Institution of Malaka Sub-distric.